A study comparing the effects of rosiglitazone and/or insulin treatments on streptozotocin induced diabetic (type I diabetes) rat aorta and cavernous tissues - ÇELİKEL, ÇİĞDEM; ELÇİOĞLU, HATİCE KÜBRA; KABASAKAL, LEVENT; ÖZKAN YENAL, NAZİYE (ELSEVIER, 2011)
Our aim was to investigate the role of oxidative stress and inflammation on the functional and biochemical changes caused by hyperglycemia in the aorta and corpus cavernosum tissues of streptozotozin diabetic rats and to determine if rosiglitazone and/or insulin treatment has any preventive effect on organ dysfunction. Wistar Albino rats were divided into 2 groups. I) Control group: a) Vehicle, 0.1 M citrate buffer, the solvent of streptozotocin injected intraperitoneally (i.p) and b) Rosiglitazone group: (4 mg/kg/day, i.p.) for 8 weeks. II) Diabetic group: streptozotocin (60 mg/kg) was administered i.p. to induce diabetes. 48 h after streptozotocin injection, animals were divided into 4 subgroups (n = 6 for each group); a) no treatment group (D), b) treated with rosiglitazone (4 mg/kg/day) (DR), c) treated with insulin (6 U/kg/day) (DI) and d) treated with insulin and rosiglitazone (DRI) for 8 weeks. At the end of the experimental period, animals were decapitated and tissue samples were collected for in vitro experiments and biochemical studies. Endothelium dependent relaxation induced by acetylcholine in the aorta and corpus cavernosum tissues were attenuated in the diabetic group, whereas phenylephrine induced contractile responses were reduced. These responses were restored after rosiglitazone and/or insulin treatment, the combination being the most efficient treatment. Malondialdehyde and TNF-alpha levels were increased in diabetic rats while glutathione levels were decreased. All treatments prevented these changes in biochemical parameters, rosiglitazone and insulin combination again being the most efficient treatment. Our results suggested that supplementing diabetic patients receiving insulin treatment with adjunct therapy of rosiglitazone may have some benefit for controlling diabetic complications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Streptozotosin; Aorta; Corpus cavernosum; Rosiglitazone; Insulin; ENDOTHELIUM-DEPENDENT RELAXATION; SMOOTH-MUSCLE RELAXATION; CORPUS CAVERNOSUM; RESISTANCE ARTERIES; OXIDATIVE STRESS; DYSFUNCTION; INFLAMMATION; IMPAIRMENT; CAVEOLIN-1; EXPRESSION